Mayor acceso con menor calidad en la educación superior: algunas evidencias desde las habilidades de los estudiantes - Yamada Fukusaki, Gustavo (2013)
In the last decade, access to higher education in Peru has increased substantially. On the other hand, the proportion of children and adolescents with adequate knowledge to their grade, reflected in learning tests, remains low and has made little progress. What has happened then with the skills of entrants to higher education? This research uses information of a novel survey that measures skills of several generations, and a difference-in-differences evaluation methodology to show some evidence of deterioration in the average level of cognitive skills of higher education students admitted in the past decade. The lower average level of selectivity in the system has helped this process, as access to private universities has gained preponderance. These results reveal that the lower skills of the last generations of students are one of the reasons for the deterioration of the quality of the professionals observed in Peru.